Spexin Hormone and Its Relationship With Age, Sex, and Smoking in Heart Attack Patients (College of Basic Education Research Journal, 2025)
Study focused on anthropometric measurements in addition to smoking , its relationship with  Spexin hormone (SPX) and its role in heart attack risk for both sexes. 91 samples were collected from people with heart attacks and 91 likewise were collected from people to be control group.  Outcomes demonstrated that  level of  hormone decreased with age, while  body mass index (BMI) increased with age for  group suffering  heart attack compared with control group,    incidence rate in males is 2.25 times higher than in females,  age is a major factor that affects hormone levels and reduces  its activity, males of all age groups usually have a higher infection rate than females of the same age groups. In addition, smokers are more susceptible to heart attacks compared to non-smokers.Finally, this study discovered a connection between a decline in spexin as well as  rise in  risk factor for heart attack, which has a strong role, especially in male smokers and those who are overweight.
Keywords: Spexin hormone (SPX); Age; Sex; Heart attack